Security for Telecommunications Networks - Traynor, Patrick; McDaniel, Patrick; Porta, Thomas La.; SpringerLink (Online service) (Boston, MA : Springer US, 2008)
Telecommunications networks are a critical component of the economic and social infrastructures in which we live. Each day, well over three billion people across the globe rely upon these systems, as their primary means of connecting to the world around them. Given the significant focus on securing critical infrastructure in recent years, Security for Telecommunications Networks creates a starting place for new researchers in the field of secure telecommunications networks. This volume not only discusses emerging threats, along with system vulnerability, but also presents the open questions posited by network evolution and defense mechanisms. This is one of the first books to discuss securing current and next generation telecommunications networks by the security community. Security for Telecommunications Networks is designed for a professional audience composed of practitioners and researchers in industry. This book is also suitable as a secondary text book or reference for advanced-level students in computer science and electrical engineering. .
Network Architecture -- Security -- Cellular Architecture -- Vulnerability Analysis -- Vulnerabilities in the Telephony -- Vulnerabilities in the Short Messaging Service (SMS) -- Vulnerabilities in Cellular Data Networks -- Vulnerabilities in Voice over IP -- Future Analyses -- Future Directions and Challenges.
Keywords: Computer science; Computer organization; Computer communication systems; Computer security; Data structures (Computer science).; Data encryption (Computer science).; Computer Science; Systems and Data Security; Computer Communication Networks; Data Encryption; Data Structures, Cryptology and Information Theory; Computer Systems Organization and Communication Networks; Electronic books